Tackling Imbalance Datasets: Methods, Techniques & Comparisons - Kumar, Shivam; Ahuja, Deepanshu; Kumar, Sandeep (International Journal of Computer Sciences and Engineering, 2023)
Over the past many years of continuous research and learning from data, i.e.duplication and Extraction continues to be a spotlight of enormous research. A classification data set with skewed class proportions is referred to as imbalanced. This term originated as a debate over the skewed distributions of binary tasks. Imbalanced data are those datasets that have an uneven distribution of observations across the target class, i.e First class category will have a very higher number of observations while the other class will have less number of observations. The emergence of the massive data era, along with the growth of machine learning and data mining (Data Science), as going deeper into the field of learning with imbalanced datasets, alongside the challenges which are emerging. Data-level methods and algorithm-level methods are repeatedly used and getting improved and popularity of hybrid approaches increased due to the extraction of earlier approaches (data level and algo level) and reduced weaknesses with powerful points. In order to advance the field of addressing imbalanced datasets and compare existing approaches and methodologies, this paper attempts to discuss the open questions and challenges that need to be resolved. This essay discusses each of them and offers ideas for potential directions for further investigation. The main issue with an unbalanced class distribution is when bad training habits cause bias in favour of the majority class. Deep learning algorithms and machine learning algorithms perform training on datasets which are underrepresented in some categories. Conventional methods advise to perform undersampling on majority class category and oversampling minority class category before the learning stage.By including learning modules with clever representations of samples from majority and minority samples, this research investigates various traditional and contemporary strategies to address this issue. The works of several researchers are compiled in a very logical approach and numerical opportunities and also future difficulties for the field`s future research are discussed.